2008
DOI: 10.1211/jpp.60.3.0003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the sequential metabolites of loteprednol etabonate in rats

Abstract: Pharmacokinetics, metabolism and excretion of two sequential inactive metabolites of the soft corticosteroid loteprednol etabonate (LE), Delta1-cortienic acid etabonate (AE) and Delta1-cortienic acid (A), have been investigated in rats. Pharmacokinetic studies (two-compartment model, 10 mg kg(-1) intra-venous bolus of AE or A) found the elimination of both AE (t(1/2)(beta), 12.46 +/- 1.18 min; CL total, 101.94 +/- 5.80 mL min(-1) kg(-1); and K el, 0.24 +/- 0.02 min(-1)) and A (t(1/2)(beta), 14.62 +/- 0.46 min;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“… 43 The chemical structure of LE is such that any drug that is not bound to the glucocorticoid receptor undergoes rapid conversion into inactive metabolites, allowing for localized, controlled suppression of ocular inflammation with minimized potential for causing unwanted side effects. 41 , 42 , 44 , 45 Studies comparing LE suspension or gel to other corticosteroids, including dexamethasone, 51 , 57 , 59 61 prednisolone, 54 56 , 58 , 79 , 80 and flurometholone, 50 , 81 , 82 have consistently found that LE has lower impact on IOP, while retaining the desired anti-inflammatory effects of a corticosteroid. A recent review by Sheppard et al of the available published data on the effect of marketed LE formulations on IOP found that LE consistently demonstrated a low propensity to elevate IOP, regardless of the formulation, dosage regimen, or treatment duration, including in known steroid responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 The chemical structure of LE is such that any drug that is not bound to the glucocorticoid receptor undergoes rapid conversion into inactive metabolites, allowing for localized, controlled suppression of ocular inflammation with minimized potential for causing unwanted side effects. 41 , 42 , 44 , 45 Studies comparing LE suspension or gel to other corticosteroids, including dexamethasone, 51 , 57 , 59 61 prednisolone, 54 56 , 58 , 79 , 80 and flurometholone, 50 , 81 , 82 have consistently found that LE has lower impact on IOP, while retaining the desired anti-inflammatory effects of a corticosteroid. A recent review by Sheppard et al of the available published data on the effect of marketed LE formulations on IOP found that LE consistently demonstrated a low propensity to elevate IOP, regardless of the formulation, dosage regimen, or treatment duration, including in known steroid responders.…”
Section: Discussionmentioning
confidence: 99%
“…This unique structure facilitates rapid metabolism of LE molecules that are unbound to glucocorticoid receptors into inactive metabolites, 41 44 allowing LE to exert the desired anti-inflammatory activity while reducing the likelihood of unwanted effects. 41 , 43 , 45 , 46 LE ophthalmic suspension 0.5% (Lotemax ® suspension; Bausch + Lomb, Bridgewater, NJ, USA) was approved in 1998 for the treatment of postoperative inflammation following ocular surgery, in addition to steroid-responsive inflammatory conditions such as seasonal allergic conjunctivitis and uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other corticosteroids, loteprednol etabonate has a unique structure, which allows it to readily penetrate cell membranes (31). In addition, it has a strong potential for glucocorticoid receptors, whereas the detached drug is rapidly converted into inactive metabolites, preventing any unwanted side-effects of ocular corticosteroids, such as intraocular pressure elevation and cataractogenesis (32). Currently, there are no significant clinical trials that have revealed positive correlations between loteprednol etabonate use and a reduction in the recurrence of pterygium, which leaves possibilities for future investigators (33).…”
Section: Loteprednol Etabonatementioning
confidence: 99%
“…11 LE is highly lipophilic, which facilitates its easy penetration through cell membranes,12 and it has been shown to have a therapeutic index more than 20-fold higher than that of other corticosteroids 13. LE was developed using “retrometabolic” engineering, to reduce its potential for adverse effects;14 it binds avidly to the glucocorticoid receptor, while the unbound drug is rapidly converted to inactive metabolites, minimizing the potential for unwanted effects, such as intraocular pressure (IOP) elevation and cataractogenesis 11,13,15,16. Studies have confirmed a lower risk of IOP elevations with LE compared with other ocular steroid compounds 11,1721…”
Section: Loteprednol Etabonatementioning
confidence: 99%